The Participation of Federal Institutes in the Internalization of On-campus Higher Education in Brazil (Research, Society and Development, 2020)
This study, first, aims to analyze how the Federal Institutes were integrated in the offer of Higher Education in Brazil. Articulately, it will presents how the process of internalization of vacancies occurred. Creating the Federal Institutes in 2008, the federal government established them as institutions of higher, basic and professional education, promoting the expansion of the number of vacancies in the country. It is a quantitative and qualitative research. Data collection was performed based on information from the National Institute for Educational Studies and Research Anísio Teixeira - INEP, through the Higher Education Census system, from 2008 to 2017. Preliminary results show that the expansion and internalization of vacancies. This contributes to the access to higher education in regions that were not previously attended.